The midwife’s professional independence in the opinion of society – condition of fetus - Iwanowicz-Palus, Grażyna; Golonka, Ewa; Bień, Agnieszka; Stadnicka, Grażyna (Nursing in the 21st Century, 2013)
THE MIDWIFE’S PROFESSIONAL INDEPENDENCE IN THE OPINION OF SOCIETY – CONDITION OF FETUSIntroduction. Normal pregnancy, proper care during pregnancy and delivery enable right physical, emotional and intellectual development of a baby and its health in adult life.Aim. The aim of the study was an attempt to find out the opinion of the Polish society about midwife’s preparation to independently evaluating the condition of fetus.Materials and methods. The study was conducted in 2011 by means of the diagnostic survey method applying questionnaire technique. The research tool was a self-constructed questionnaire, which was conducted among 293 women and 212 men who live in the East region of Poland.Results. The study showed that in respondents’ opinion a midwife is prepared to independently provide health services concerning evaluation of the condition of fetus including periodical listening to the fetal heart rate (82.77%), continuous listening to the fetal heart rate (74.65%), assessing of fetal activity – fetal movement (79.20%), doing CTG (72.47%) and interpreting CTG (55.84). Respondents who took part in the survey were not convicted that a midwife is prepared to independently perform ultrasound examination (38.81%: “rather no” - 23.37%, “definitely no” - 15.45%).Conclusions. A midwife is prepared to independently provide health services concerning evaluation of the condition of fetus in cluding periodical listening to the fetal heart rate, continuous listening to the fetal heart rate, doing and interpreting CTG, assessing of fetal activity. A mid wife isn’t pre pared to independently perform ultrasound examination.